Peranan Endorse “Aice” Terhadap Keputusan Pembelian - Charlie Montalvo; Chevi Revahingis; Henny Henny; Monica Monica; Shendy Shendy (Institut Nalanda, 2024)
There are various ways to do marketing carried out by companies and one of them is promotion, one of the current trendy promotional techniques is to use endorsements which can then influence consumer purchasing decisions. This study was conducted with the aim of knowing how much influence endorsement has on purchasing decisions on ice cream brand aice in Medan. This research is descriptive research with a quantitative approach. The sample in this study amounted to 35 community respondents who had seen aice advertisements with random sampling techniques regardless of strata in the population or what is commonly referred to as simple random sampling. Data was collected through a questionnaire via google form. The results showed that Endorsement had a partially significant effect on Purchasing Decisions with a t value of 8.873> t table 1.69092 and Endorsement had a simultaneous effect on Purchasing Decisions with an F value of 78.731> F table 2.86 with a regression coefficient value of 83.9%.